COVID-19 discharge and follow-up recommendations - Abdelnabi, Mahmoud (Proc (Bayl Univ Med Cent), 2020)
Currently, the world is facing a global pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), also known as COVID-19. So far, there are no clear recommendations regarding hospital discharge and aftercare for COVID-19. Here, we briefly discuss the current understanding of recommendations for discharge criteria, discharge treatment regimens, and follow-up.